Blood transfusion in cardiac surgery: Does the choice of anesthesia or type of surgery matter? - Nešković Vojislava; Milojević Predrag; Unić-Stojanović Dragana; Slavković Zoran (Vojnosanitetski Pregled)
Background/Aim. In spite of the evidence suggesting a significant morbidity associated with blood transfusions, the use of blood and blood products remain high in cardiac surgery. To successfully minimize the need for blood transfusion, a systematic approach is needed. The aim of this study was to investigate the influence of different anesthetic techniques, general vs combine epidural and general anesthesia, as well as different surgery strategies, on-pump vs off-pump, on postoperative bleeding complications and the need for blood transfusions during perioperative period. Methods. Eighty-two consecutive patients scheduled for coronary artery bypass surgery were randomized according to surgical and anesthetic techniques into 4 different groups: group 1 (patients operated on off-pump, under general anesthesia); group 2 (patients operated on off-pump, with combined general and high thoracic epidural anesthesia); group 3 (patients operated on using standard revascularization technique, with the use of extracorporeal circulation, under general anesthesia), and group 4 (patients operated on using standard revascularization technique, with the use of extracorporeal circulation, with combined general and high thoracic epidural anesthesia). Indications for transfusion were based on clinical judgment, but a restrictive policy was encouraged. Bleeding was considered significant if it required transfusion of blood or blood products, or reopening of the chest. The quantity of transfused blood or blood products was specifically noted. Results. None of the patients was transfused blood or blood products during the surgery, and as many as 70/81 (86.4%) patients were not transfused at all during hospital stay. No difference in postoperative bleeding or blood transfusion was noted in relation to the type of surgery and anesthetic technique applied. If red blood cells were transfused, postoperative bleeding was the most influential parameter for making clinical decision. Conclusion. No influence of off-pump surgery or epidural anesthesia on blood transfusion requirements during a perioperative period was confirmed by this study. It seems, however, that encouraging lower hemoglobin triggers in clinical decision-making could result in less transfusions during surgery or hospital stay.